2015
DOI: 10.1002/adfm.201503666
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Supported Cobalt Phosphide Mesoporous Nanorod Arrays: A Flexible and Bifunctional Electrode for Highly Active Electrocatalytic Water Reduction and Oxidation

Abstract: 7337wileyonlinelibrary.com energy and the development of regenerative fuel cells and rechargeable metal-air batteries. [1][2][3][4] Note that overpotentials originating from the polarization phenomenon occurring at the electrodes induce a larger voltage window than the theoretical minimum one (1.23 V) to afford thermodynamic driving force. [ 5,6 ] As such, the sluggish apparent reaction kinetics necessitates the utilization of noble-metal-based electrocatalysts to achieve respectable performance, i.e., Pt for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
418
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 718 publications
(451 citation statements)
references
References 64 publications
32
418
1
Order By: Relevance
“…The OER activity of 20-NMWNT is significantly improved in 1 M NaOH and shows an onset potential of only $1.5 V. The overpotentials required for OER current density of 10 mA cm À2 (denoted as N OER10 ) are measured to be 360 mV and 320 mV in 0.1 and 1 M NaOH, respectively. These values are comparable to those of the recently reported highly active transition metals [17,25,26,[44][45][46] and superior to the most active metal free catalysts [5,24,33,37,3 8,42,47-50] for OER (for more comparison see Table S2). It is noteworthy that the performance of 20-NMWNT is comparable to that of the most active metal-free catalysts reported very recently including N,S-CNT [47] (N OER10 of 360 mV in 1 M KOH), the most active N-doped metal-free catalyst, N-doped graphene nanoribbons (N-GRW) which has been recently reported by Liu et al [37], showing N OER10 of 360 mV in 1 M KOH, and also nitrogen, phosphorus and oxygen tri-doped porous graphite carbon@oxi-dized carbon cloth (ONPPGC/OCC) [38] developed as a metal-free bifunctional electrocatalyst but requiring significantly higher N OER10 of 410 mV in 1 M KOH.…”
Section: Oer Electrocatylitic Activitysupporting
confidence: 73%
“…The OER activity of 20-NMWNT is significantly improved in 1 M NaOH and shows an onset potential of only $1.5 V. The overpotentials required for OER current density of 10 mA cm À2 (denoted as N OER10 ) are measured to be 360 mV and 320 mV in 0.1 and 1 M NaOH, respectively. These values are comparable to those of the recently reported highly active transition metals [17,25,26,[44][45][46] and superior to the most active metal free catalysts [5,24,33,37,3 8,42,47-50] for OER (for more comparison see Table S2). It is noteworthy that the performance of 20-NMWNT is comparable to that of the most active metal-free catalysts reported very recently including N,S-CNT [47] (N OER10 of 360 mV in 1 M KOH), the most active N-doped metal-free catalyst, N-doped graphene nanoribbons (N-GRW) which has been recently reported by Liu et al [37], showing N OER10 of 360 mV in 1 M KOH, and also nitrogen, phosphorus and oxygen tri-doped porous graphite carbon@oxi-dized carbon cloth (ONPPGC/OCC) [38] developed as a metal-free bifunctional electrocatalyst but requiring significantly higher N OER10 of 410 mV in 1 M KOH.…”
Section: Oer Electrocatylitic Activitysupporting
confidence: 73%
“…The high-resolution P 2p spectrum shows two main peaks at 134.1 and 129.3 eV ( Fig. 2(d)), with the lower binding energy (BE) peak corresponding to metal phosphides, and the other reflecting the oxidized metal phosphate species on the surface, arising from exposure of superficial NiCoP to air [23,29]. After peak deconvolution of the Co 2p 3/2 core level region, two main peaks appear at 778.8 and 781.7 eV, with the peak located at 794.2 eV assigned to oxidized metal phosphate ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, MPCs have been reported to show good catalytic OER performance, attributable to the formation of metal oxo/hydroxo species on the catalyst surface, which create a heterostructure with high OER activity [12,22]. While significant progress has been made in the study of binary transition metal phosphides as bifunctional catalysts [12,22,23], the application of ternary metal phosphides in hydrogen or oxygen evolution reactions has been scarcely reported, to the best of our knowledge. In addition, previous spectroscopic and theoretical studies demonstrated that the incorporation of additional metal atoms into HER and OER catalysts is crucial for enhancing their electrocatalytic activity by tuning of the electronic structure [24][25][26][27].…”
mentioning
confidence: 98%
“…Although a variety of non-noble metal-based nanostructured materials such as Mo 2 C/MoO 2 [11], Co 9 S 8 /graphene [12], CoPS [13], CoMoS [14], NiMoN [15] have been reported, the facts are still far from satisfactory since these materials are either for oxygen evolution reaction (OER) catalysts working in strongly alkaline conditions or for hydrogen evolution reaction (HER) catalysts operating in strongly acidic mediums due to the thermodynamic convenience [5,[16][17][18]. The inferior efficiency caused by the disparity of the stability and activity for the same catalyst system in the operating pH ranges [19,20] limits the practical implementations of these materials as a catalytic electrode in an integrated electrolyser. Therefore, a formidable challenge for electrocatalytic water splitting is to explore and design bifunctional catalysts that can work well for both HER and OER in the same alkaline medium to accomplish overall water splitting.…”
Section: Introductionmentioning
confidence: 99%